PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI SMAN 1 KAMANG MAGEK - Fernando, Wahyu Prima; Delsi K, Delsi K; febriana, Rina (Pendidikan Matematika, 2014)
ABSTRACT This research is motivated by the understanding of the mathematical concept of class XI students of SMAN 1 Kamang Magek are still low and students are less active in the learning process. This study aims to determine whether students understanding of mathematical concepts by implementing Cooperative Learning Model Type of Student Teams Achievement Division (STAD) better than the students understanding of mathematical concepts with conventional learning. This research is an experimental study. The population in this study was a class XI student of SMAN 1 Kamang Magek 2013-2014 school year. Sampling technique was randomly selected and the experimental class IPA2 XI and class control IPA1 . Instrument used in this study is the understanding of the concept in the form of a test with a reliability test essay R11 = 0.73. Hypothesis test results, obtained using a t-test p-value equal to 0.0038 which is smaller than (Î±) = 0:05, then the hypothesis in this study received, so it can be concluded that the students understanding of mathematical concepts with the model type of cooperative learning Student Teams Achievement Division (STAD) better understanding of the mathematical concepts with conventional learning students in class XI Science SMAN 1 Kamang Magek.